Implementasi metode Tilawati dengan nada Rost terhadap kualitas tahfizh juz Amma - Rohmah, Sufi Fajriyatur; Pesha, Indry Nirma Yunizul; Triwoelandari, Retno (Tawazun: Jurnal Pendidikan Islam, 2023)
This research is motivated by several problems that occur in learning activities at TPA Tahfizh At-Taqwa, so that the activities and results of Tahfizh learning obtained by students have not reached the set targets. Based on observations it is known that in following the learning process and the lack of teacher variation in using methods affects the low student learning outcomes. The purpose of this study was to determine the implementation of the Tilawati Method with Rost Tones on the Quality of Tahfizh Juz Amma students. The research method used is a qualitative method with a field study approach, the primary data source is the teacher and validation is by triangulation of sources. The data collection technique was observation and interviews with a research background at the Tahfizh At-Taqwa TPA, the research subjects were students of the Tilawati Qur'an class, each class numbering 15 students. The researcher made observations of the teacher's activities including the implementation of the opening activities, the implementation of the core activities, the teacher's learning approach, the arrangement of the learning class and the implementation of the evaluation. students read according to recitation, and students' ability to pronounce letters according to their makhraj. The application of the Tilawati method at the Tahfizh At-Taqwa TPA as a whole is in accordance with the provisions set by the Tilawati institution, but there are several things that are adjusted and combined with the conditions and programs at the Tahfizh At-Taqwa TPA, such as when learning is given writing material and supporting materials for memorizing prayers, Hadith, and Arabic. Nonetheless, the application of the Tilawati method to learning Tahfizh Juz Amma at the Tahfizh At-Taqwa TPA remains in accordance with the provisions and basic principles of Tilawati. Abstrak Penelitian ini di latar belakangi oleh beberapa permasalahan yang terjadi dalam kegiatan pembelajaran di TPA Tahfizh At-Taqwa, sehingga aktivitas dan hasil pembelajaran Tahfizh yang diperoleh santri belum mencapai target yang telah ditetapkan. Berdasarkan observasi diketahui bahwa dalam mengikuti proses pembelajaran dan kurangnya variasi guru dalam menggunakan metode mempengaruhi rendahnya hasil belajar santri. Tujuan penelitian ini untuk mengetahui implementasi Metode Tilawati Dengan Nada Rost Terhadap Kualitas Tahfizh Juz Amma santri. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan studi lapangan, sumber data primernya adalah guru dan validasi dengan triangulasi sumber. Teknik pengumpulan datanya dengan observasi dan wawancara dengan latar penelitian di TPA Tahfizh At-Taqwa , subyek penelitiannya adalah santri kelas Tilawati Alquran yang setiap kelasnya berjumlah 15 santri. Peneliti melakukan observasi terhadap aktivitas guru meliputi pelaksanaan kegiatan pembuka, pelaksanaan kegiatan inti, pendekatan pembelajaran oleh guru, penataan kelas pembelajaran dan pelaksanaan evaluasi, selain observasi aktivitas guru, peneliti juga mengamati aktivitas siswa dalam pembelajaran meliputi kelancaran membaca Alquran siswa, kemampuan membaca siswa sesuai dengan tajwid, dan kemampuan siswa dalam melafalkan huruf sesuai dengan makhrajnya. Penerapan metode Tilawati di TPA Tahfizh At-Taqwa secara ke seluruh sesuai dengan ketentuan-ketentuan yang telah ditetapkan oleh lembaga Tilawati, namun terdapat beberapa hal yang disesuaikan dan dikombinasikan dengan keadaan dan program di TPA Tahfizh At-Taqwa, seperti pada saat pembelajaran diberikannya materi menulis dan materi penunjang hafalan doa-doa, Hadist , dan Bahasa Arab. Meskipun demikian, penerapan metode Tilawati pada pembelajaran Tahfizh Juz Amma di TPA Tahfizh At-Taqwa tetap sesuai dengan ketentuan dan prinsip dasar Tilawati.